IMPLEMENTASI KEBIJAKAN PENERTIBAN PEDAGANG KREATIF LAPANGAN DI KOTA PALU - Fitrah, Fitrah (Katalogis, 2017)
This study aims to find out how the Implementation of Policy in the Regulation of Creative Field Traders at the Office of Police Unit of Pamong Praja City of Palu. The data used in this study is the primary data obtained by observation data and in-depth interviews. The method used in this study is a qualitative method with the determination of informants using purposive techniques. The research technique using interactive model. Based on the four indicators of research, namely Communication, Resource, Disposition, Organizational Structure, showing in the implementation of Policy Implementation In the Regulation of Creative Field Traders At the Office of Police Unit of Pamong Praja City of Palu, has not run maximally, where indicator of communication and resources has not run As it should, because the socialization has not run in accordance with expectations where there is still no good communication between Satpol PP with policy goals, in the form of socialization routinely and information provided. As well as constraints from the aspect of existing equipment resources in the indicator Resources can be concluded not yet sufficient where the volume number of Satpol PP officers is inversely proportional to the means owned. The other two indicators have been running in accordance with the expectations for the attitude disposition aspect taken by Satpol PP has been in accordance with the steps to be taken and the bureaucratic structure indicator that has two aspects of both the SOP and the division of authority has been implemented properly.